Take Control of Podcasting - Affleck, Andy (Take Control Books, 2020)
Create your own podcast on a Mac, iPhone, or iPad Start podcasting or take your podcast to the next level with start-to-finish guidance from Andy Affleck. You'll learn tricks of the trade as you assemble your hardware and software, make recordings, edit and mix the audio, and encode and publish your shows. This book covers all the steps needed to make a podcast using a Mac, iPhone, iPad, or iPod touch. Create your own podcast-or improve an existing podcast-using your Mac, iPhone, iPad, or iPod touch! This book walks you through every step of the process, from choosing equipment and software through recording, editing, mixing, and polishing. Once your audio is in the can, you'll find real-world advice and steps for encoding and publishing your episodes. This book replaces and updates Andy's earlier title, Take Control of Podcasting on the Mac , with up-to-date instructions and complete coverage of iOS and iPadOS devices. The book includes more than dozen sound samples from various combinations of mics, positions, filters, and processing, so that you can hear the differences before you buy any special gear. Take Control of Podcasting provides the help you need for creating podcasts on a Mac, iOS, or iPadOS device: Plan your podcast. Decide on a topic and format, decide on a production schedule, learn common terms and techniques, and think about monetization strategies. Choose the right mic, headphones, and other equipment. Pick out audio gear while considering your budget and studio (or mobile!) needs. Plus, you'll learn if you should buy additional audio hardware, like a breakout box or mixer, and find an explanation (with photos) of the main cable types that you'll come across. Pick audio software. Apps discussed at length include GarageBand for Mac and iOS/iPadOS, Audacity, Audio Hijack, Ferrite Recording Studio, and Voice Record Pro. Apps that are discussed briefly include Amadeus Pro, Ecamm Call Recorder, Fission, Izotope RX Elements, Loopback, Sound Studio, SoundSoap, and The Levelator. The book also mentions using Zoom, FaceTime, and Skype for interviews and remote recording, as well as various web-based podcasting platforms. Learn key recording tips. Find advice about how to prepare for and conduct a successful interview, plus get a few essential tips for using a mic well. Record in the studio or the field. Get step-by-step recording directions for GarageBand for Mac and iOS/iPadOS, as well as Audacity, Ferrite Recording Studio, Voice Re...